Evaluation of Oral Hygiene Status in Patients Using Clear Aligners Versus Fixed Orthodontic Appliances (Academia Journal of Medicine, 2026)
Background:Orthodontic appliances can adversely affect oral hygiene by promoting plaque accumulation and gingival inflammation. Fixed orthodontic appliances are associated with increased plaque-retentive areas, whereas clear aligners, being removable, may facilitate better oral hygiene maintenance. Aim:To evaluate and compare the oral hygiene status in patients undergoing orthodontic treatment with clear aligners and fixed orthodontic appliances. Materials and Methods:A comparative clinical study was conducted on 60 orthodontic patients divided into two groups: Group A comprised 30 patients treated with clear aligners, and Group B comprised 30 patients treated with fixed orthodontic appliances. Oral hygiene status was assessed using the Plaque Index (Silness and Löe) and Gingival Index (Löe and Silness). The collected data were statistically analyzed using the independent t-test. Results:The mean plaque and gingival index scores were significantly lower in the clear aligner group compared to the fixed appliance group (p < 0.05), indicating superior oral hygiene and gingival health among aligner-treated patients. Conclusion: Patients treated with clear aligners demonstrated better oral hygiene status than those treated with fixed orthodontic appliances. Clear aligners may therefore be considered a favorable treatment option for patients where maintenance of periodontal health is a priority.
Keywords: Clear aligners, fixed orthodontic appliances, oral hygiene, plaque index, gingival index